Теория бухгалтерского учета: учебное пособие - Сидорова Н. П. Наталья Петровна; Макарычев В. А. Владимир Алексеевич; Мишина З. А. Зинаида Александровна; Игошина Ю. А. Юлия Александровна; Шамин А. Е. Анатолий Евгеньевич; Фролова О. А. Ольга Алексеевна (Старый Оскол, ТНТ, 2021)
Авт. указаны на обороте тит. л.